Design and construction requirements for façade integration of building services: Discussion of main perceived barriers from an exploratory expert survey - Prieto Hoces, Alejandro Ignacio; Klein, Tillman; Knaack, Ulrich; Auer, Thomas (A+BE | Architecture and the Built Environment, 2018)
The integration of decentralised building services into façade components presents advantages from functional and constructional standpoints. However, this integrated approach has not been massively implemented, having only stand-alone buildings and façade concepts as examples.This chapter delves into the requirements for integration within the façade development process, aiming to identify the main perceived problems for building services integration in facades at design, production and assembly stages. The employed method was an exploratory survey addressed to professionals involved in the development of façade systems for office buildings, at different stages, in order to generate new knowledge based on practical experience. The survey was conducted from mid-September to mid-November, 2015 and was distributed both as an online form and in printed format among several professional networks. Results show that the main problems refer to the overall process, particularly regarding coordination issues among different disciplines and stakeholders, while other problems such as costs and lack of knowledge, while still relevant, have more impact on particular stages. Among relevant problems related to the products themselves, the results show physical integration issues during production and assembly stages, and barriers derived from unreliable performance and technical limitations of current products to be integrated in façade systems.